Tulsi: From the desk of a periodontist - Malvika Singh (Wolters Kluwer Medknow Publications, 2021)
Introduction: Role of tulsi in periodontal disease is a polymicrobial infection primarily caused by periodontal pathogens existing within the subgingival plaque. The conventional method of lowering the bacterial load in the periodontal pocket constitutes scaling and root planning, but to prevent recolonization the use of adjunctive methods has been advocated. Tulsi (Ocimum sanctum) is being widely used in dentistry in the form of mouthwashes, dentifrice, gels, and oral irrigants. Objective: The objective behind writing this article was to assess the relevance of and effectiveness of Tulsi (O. sanctum) in the treatment of periodontal disease. Data Source: Internet database Medline/PubMed search for word "Tulsi" resulted in 1000 articles. Review Methods: Articles with Medline/PubMed were only considered in writing this review. The result showed that Tulsi has been widely used as a mouthwash, dentifrice, and oral irrigant in the field of periodontics. Conclusions: Although highly effective, the use of Tulsi has not been popularized in today's day and age and needs to be done the same.